Hannah Arendt, the problem of the absolute and the paradox of constitutionalism, or ‘How to restart time within an inexorable time continuum’ - Lindsay, Adam (SAGE Publications, 2017)
Contemporary theorists of constituent power recognise a tension in which the omnipotent novelty of constituent power is necessarily policed by constituted power. Beginning with Arendt’s claim that the categories of constitutional stability and political novelty should be thought together rather than treated as oppositional, this article presents an interpretation of her work that seeks to address this ‘paradox of constitutionalism’. Whilst commentators have come to assert that Arendt repudiates ‘absolutes’ in favour of an account of ‘relative beginnings’, this article demonstrates that Arendt’s argument involves a critical redescription of the absolute, rather than a repudiation. This is significant, for it illuminates the manner in which her account of founding seeks to dismantle the commonplace temporalisations we attribute to our political vocabulary. This is employed to argue that particular stylings of absolutes naturalise the appearance of the new only as temporal ruptures, allowing us to get a handle upon the paradox of constitutionalism, and to think tentatively beyond this paradigm.